PENGGUNAAN METODE CERITA DONGENG TERHADAP PERKEMBANGAN MINAT PADA ANAK TK - Fitrika; Eniwati Khaidir (QURROTI, 2020)
The purpose of this study was to determine how the development of interest in kindergarten children through the story telling method. This research uses qualitative research. The subjects in this study were 1 teacher and 31 kindergarten children. The sample used is non random sampling. While the instruments used are through interview techniques, documentation and observation. Based on the results of research in chapter IV, it shows that the development of interest in children has increased positively. Before the research was carried out, there were 10 children who completed the study with a percentage of 32.25% with the "Less" score category. Furthermore, after the first study, the children who completed the overall increase to 19 children with a percentage of 61.29% with the value category "Enough", and in the second study the children who completed the total were 25 children or with a percentage of 80.64% with the value category "Good". Thus it can be concluded that the use of the story telling method is effective in developing interest in kindergarten children.